Use of general practice before and after mild traumatic brain injury: a nationwide population-based cohort study in Denmark - Galili, Stine Fjendbo (BMJ Open, 2017)
OBJECTIVES: Traumatic brain injury (TBI) is commonly seen in the emergency department (ED). Approximately 85%–90% of TBIs are mild (mTBI). Some cause symptoms such as headache, dizziness, anxiety, blurred vision, insomnia and concentration difficulties, collectively known as postconcussion syndrome (PCS). Some studies suggest that recovery from mTBI is complete. Others find that symptoms persist for months, even years. The aim of this study was to describe the use of general practice, before and after mTBI, as a proxy for symptoms in a large cohort. DESIGN: Nationwide population-based matched cohort study. SETTING: Danish EDs and general practice. PARTICIPANTS: All patients (aged ≥18 years), first-time diagnosed with mTBI in a Danish ED between 1 January 1998 and 31 December 2010 (n=93 517). Ten reference persons per patient with mTBI were randomly matched on gender, age and general practice (n=935 170). PRIMARY OUTCOME: Overall use of general practice; consultations relating to mental and physical health. RESULTS: We found higher use of general practice during the first year after mTBI for all ages, both genders and all types of contacts. Age 18–40 years: women, incidence rate ratio (IRR) 1.59 (95% CI 1.57 to 1.61); men, IRR 1.82 (95% CI 1.80 to 1.85). Age 41–65 years: women, IRR 1.75 (95% CI 1.72 to 1.78); men, IRR 1.85(95% CI 1.82 to 1.89). Age 66+ years: women, IRR 1.55 (95% CI 1.52 to 1.58); men, IRR 1.55 (95% CI 1.51 to 1.59). After the first year, the use decreased to the level before mTBI. Individuals with mTBI and higher use of general practice before mTBI had lower socioeconomic status and more comorbidities (P<0.001). CONCLUSIONS: The use of general practice was higher in the first year after mTBI, specifically in the first 3 months. Patients with mTBI had different healthcare-seeking behaviour several years before diagnosis than their matched reference persons. Pretraumatic morbidity should be considered in the evaluation of PCS.